AUTISM: 7ESPECIFIC RESTORE POINTS CHIP'S DISCONNECTED (Fiep Bulletin - online, 2019)
Autism (CC Ceci, Ee- And Reverse, Gg- G Mater) is characterized by disconnection of the third, fifth and seventh pairof CCM's Reverse (Contractile Cells Mater), the closing six chip's in the body; the first chip is the heart (heart palace brand, isautonomous, only disconnects by death), the second is the second cervical vertebra (Axis, "majestic" all-seeing, is the third eye inthe body) the third chip is at the junction in both eyes, more precisely in the optic nerve, the fourth and fifth are the biceps, the sixthand seventh are in heels; the autistic child. that may have been born disconnected or became so at some point after birth, or evenin your adult life is possible this shutdown in those couples who happens to be a rejection of a genetic inheritance Pater on themater genetic inheritance or the reverse , the most common being the first that is autistic boys in greater quantitative justifying arejection of Pater heritage on the mater, and always in the third, fifth and seventh pair of CCM's that Genetics spoke the third, fifthand seventh chromosome pair . This shutdown depends on the autism degree are just three:Grade 1-Beta-Ceci (Aa Bb Cc) Record (affects vision, hearing and speech, data processing);Grade 2-E Reverse (Ee) Less Grave (affects muscles and nerves) cognitive remains intact;Grade 3-G Mater (Gg) Very Severe (with disconnection of three pairs chip's Cc-Ee-Gg CEG).What the authors call Asperger Syndrome is actually autism grade 2 and Reverse (Ee) which affect muscles andnerves, keeping intact all intellectual cognitive network.
Keywords: Autism; eletriplóide- Chip's desconectados- Restoration